2015
DOI: 10.1021/acs.orglett.5b02060
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Biogenesis of Roussoellatide, a Dichlorinated Polyketide from the Marine-Derived Fungus Roussoella sp. DLM33

Abstract: The structure of the fungal metabolite roussoellatide (1) has been established by spectroscopic and X-ray diffraction analyses. Results from feeding experiments with [1-(13)C]acetate, [2-(13)C]acetate, and [1,2-(13)C]acetate were consistent with a biosynthetic pathway to the unprecedented skeleton of 1 involving Favorskii rearrangements in separate pentaketides, subsequently joined via an intermolecular Diels-Alder reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 41 publications
(57 reference statements)
0
22
0
Order By: Relevance
“… 22 , 23 Based on the outcome of careful stable isotope labeling experiments, a Favorskii-like reaction has also been proposed to occur during biosynthesis of the fungal polyketide metabolite roussoellatide. 24 …”
Section: Discussionmentioning
confidence: 99%
“… 22 , 23 Based on the outcome of careful stable isotope labeling experiments, a Favorskii-like reaction has also been proposed to occur during biosynthesis of the fungal polyketide metabolite roussoellatide. 24 …”
Section: Discussionmentioning
confidence: 99%
“…also the reduced forms 2 c and 2 d )], produced by Helminthosporium velutinum ], the palmaenones ( 3 a and 3 b , Lachnum palmae ), roussoellatide ( 4 , Roussoella sp. ), cryptosporiopsinol ( 5 , Coniothyrium sp. ), cryptosporiopsin ( Phialophora asteris f. sp.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional labeling experiments have provided evidence of these compounds’ unique biosynthesis. The incorporation of 14 C‐ and 13 C‐labeled acetate into 1 , 4 , and 5 showed that they are biosynthesized by way of a polyketide pathway (Scheme and Figure S1 in the Supporting Information) . The effective incorporation of 6‐hydroxymellein ( 6 ) into 1 and 5 showed that 6 is a very plausible biosynthetic intermediate .…”
Section: Introductionmentioning
confidence: 99%
“…All four systems contain enzymes with differently constructed and programmed KR domains. The TerAB‐type architecture appears relatively common, being also known to be involved in the biosynthesis of other 6‐HM‐derived compounds such as roussoellatide, [41] cyclohelminthols, and palmaenones [17] . It remains to be seen whether nature also uses this architecture in other systems.…”
Section: Discussionmentioning
confidence: 99%